Homoseksualitas Dalam Al-Qur’an dan Implikasinya Terhadap Maqashid Qur’an: Telaah Atas Pemikiran Ibnu ‘Asyur Dalam Tafsir - Deki Ridho Adi Anggara; Ridho, Muh Makhrus Ali; Dwi Aprilianto; Iqro Fachrul Rozi (Universitas Islam Lamongan, 2024)
Homosexual is a sexual perversion, and this treatment was first carried out by the prophet Lut A.S called the Liwat or Sodom, and their treatment is mentioned in 4 surah called al-Fahisyah, Mujrimin, Musrifin, Mufsidin, and Tajhalun, from these sentences show that homosexual behavior is completely contrary to the nature of Man and Maqashid of Quran which is the reason for the prohibition of despicable acts, and one of the mufassir who focused his interpretation into the Maqashid of Quran was Thahir Ibn Asyur. and the article attempts to examine how the prohibition of homosexuality in the Qur'an and its effect on the Maqashid of Quran, according to Thahir Ibn Asyur. For this reason, the Descriptive and Analysis method, the Descriptive method is used to describe the object of the collected data, and the Analysis method is used to analyze the collected data, so as to explain how Thahir Ibn Asyur's views in the Prohibition of Homosexuality and its influence on Maqashid of Quran. The result is that the prohibition of homosexuality greatly affects the Maqashid of Quran according to Thahir Ibn Asyur that is to damage the aqidah (Ishlahul I'tiqad wa ta'lim al-aqdi as-shohih), corrupting Akhlaq (Tahdzibu al-Akhlaq), violating the Shari'ah (at-Tasyri'), destroying unity (Siyasatu al-Ummah), the ungodly (al-Qisas wa akhbar ummah as-Salifah), the example of (the ungodly (at-Ta'lim fima yunasibu halati 'asri al-Mukhotobin), And itis the prohibition of homosexuality that maintains the balance of the Maqashid of Quran.